2016
DOI: 10.1111/febs.13831
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of spleen tyrosine kinase in complex with novel inhibitors: structural insights for design of anticancer drugs

Abstract: The atomic coordinates and structure factors for human SYK are in the Protein Data Bank under accession codes 4XG2 (inhibitor-free form), 4XG3 (G206), 4XG4 (G207), 5GHV (O178), 4XG6 (O194), 4XG7 (O259), 4XG8 (O272), and 4XG9 (O282).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…In addition, SYK has been recently recognized as a prosurvival factor in breast cancers, as well as hematopoietic malignancies (Lee et al, 2016b), representing a strong candidate for anticancer therapy (Geahlen, 2014). In fact, fostamatinib, cerdulatinib, and entospletinib, as Syk inhibitors, are under clinical investigation as single or adjuvant agents, in certain types of leukemia (Coffey et al, 2014; Sharman et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SYK has been recently recognized as a prosurvival factor in breast cancers, as well as hematopoietic malignancies (Lee et al, 2016b), representing a strong candidate for anticancer therapy (Geahlen, 2014). In fact, fostamatinib, cerdulatinib, and entospletinib, as Syk inhibitors, are under clinical investigation as single or adjuvant agents, in certain types of leukemia (Coffey et al, 2014; Sharman et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Identifying the molecular interaction of the potential inhibitors with the target protein is the key finding of the ligand and structure-based drug discovery reports. Lee et al demonstrated that the SYK ATP-binding site can be divided into four subsites: the hinge region, the glycine-rich loop, the DFG motif, and the activation loop (Figure 3) (Lee et al, 2016). The average structures of complexes calculated from MD simulations were superimposed to study the binding mode.…”
Section: Binding Mode Analysismentioning
confidence: 99%
“…Molecular docking was carried out for compound 4a, as it showed the most significant anticancer activity against T-47D cancer cell line on, a Core 2 duo 2.20 GHz workstation, 3 GHz memory with windows 7 operating system using molecular operating environment (MOE 2008.10 software) [43]. The crystal structure of the complex of an inhibitorbound tyrosine kinase was downloaded from protein data bank (PDB ID: 4XG7) [44] which has been retrieved from www.rcsb.org [45], and was targeted in the docking experiments. The target was prepared for docking by 3D-protonation and partial charges were computed with subsequent energy minimization and using MOE default parameters under CHARMM27 (an all-atom forcefield parameterized for proteins, DNA and RNA).…”
Section: Molecular Dockingmentioning
confidence: 99%